Tricuspid annuloplasty in ischemic cardiomyopathy patients undergoing restrictive mitral annuloplasty - Yusuke Misumi; Satoshi Kainuma; Daisuke Yoshioka; Takuji Kawamura; Ai Kawamura; Shin Yajima; Shunsuke Saito; Takashi Yamauchi; Masaki Taira; Kazuo Shimamura; Shigeru Miyagawa (Frontiers in Cardiovascular Medicine)
BackgroundWe elucidated the impact of concomitant tricuspid annuloplasty (TAP) on postoperative tricuspid regurgitation (TR), pulmonary hypertension (PH) and survival in patients with ischemic cardiomyopathy undergoing restrictive mitral annuloplasty (RMA).MethodsThis study included 234 patients with ischemic cardiomyopathy (LV ejection fraction ≤40%) who underwent RMA. Of them, 114 (49%) underwent concomitant TAP for secondary TR. The primary endpoint was freedom from significant recurrence (i.e., moderate or greater) and progression (≥2+ grades) in TR. The secondary endpoints were postoperative pulmonary artery systolic pressure (sPAP) and overall survival.ResultsThe 30-day mortality was not different (0.9% vs. 0.8%, P = 0.97), despite higher EuroSCORE II score (median, 9.3% vs. 7.2%, P = 0.016) for TAP group. At baseline, TAP group had higher TR grades (2.4 ± 0.8 vs. 1.4 ± 0.6, P < 0.001) and sPAP (51 ± 16 vs. 44 ± 12 mmHg, P < 0.001). At 5-year post-surgery, RMA with TAP demonstrated higher freedom from recurrence or progression of TR (91 ± 3% vs. 81 ± 4%, log-rank P = 0.036), yielding nearly identical sPAP (42 ± 18 vs. 40 ± 16 mmHg, P = 0.54). Multivariable analysis demonstrated concomitant TAP was independently associated with freedom from significant recurrence in TR. Overall survival were not different between the groups (P = 0.74).ConclusionsIn patients with ischemic cardiomyopathy, concomitant TAP did not increase operative mortality and better reduced TR, resulting in comparable PH severity and long-term survival, compared to RMA alone.